2022
DOI: 10.1016/j.prrv.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of mHealth monitoring of pediatric bronchial asthma before and during COVID-19 pandemic

Abstract: Mobile (m) Health technology is well-suited for Remote Patient Monitoring (RPM) in a patient’s habitual environment. In recent years there have been fast-paced developments in mHealth-enabled pediatric RPM, especially during the COVID-19 pandemic, necessitating evidence synthesis. To this end, we conducted a scoping review of clinical trials that had utilized mHealth-enabled RPM of pediatric asthma. MEDLINE, Embase and Web of Science were searched from September 1, 2016 through August 31, 2021. Our scoping rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“… 37 Although telemonitoring has not yet shown conclusive superiority, 46 its potential and use have rapidly increased during the COVID-19 pandemic, 6 whereas numerous approaches are being explored. Although the usefulness and reliability of traditional tools for between-visit monitoring, such as diary cards and peak expiratory flow measurements, have been challenged, 47 there is much promise in mHealth and eHealth disease activity tracking, 48 as well as development of smart devices for medication adherence. 49 According to our findings, this innovation scene has only reached a small proportion of patients; nevertheless, there is high expectation toward the inclusion of such tools in an ideal setting.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Although telemonitoring has not yet shown conclusive superiority, 46 its potential and use have rapidly increased during the COVID-19 pandemic, 6 whereas numerous approaches are being explored. Although the usefulness and reliability of traditional tools for between-visit monitoring, such as diary cards and peak expiratory flow measurements, have been challenged, 47 there is much promise in mHealth and eHealth disease activity tracking, 48 as well as development of smart devices for medication adherence. 49 According to our findings, this innovation scene has only reached a small proportion of patients; nevertheless, there is high expectation toward the inclusion of such tools in an ideal setting.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Erwachsenen hat sich Telemonitoring bereits bei vielen chronischen Erkrankungen bewährt. Für chronische pädiatrische Erkrankungen ist dessen Evidenz bisher auf wenige Studien begrenzt [22].…”
Section: Versorgungsstrukturen Und -Lückenunclassified
“…They included five reviews in their study and found that interventions delivered via mHealth might be effective in increasing physical activity of older people in the short term. Dauletbaev et al [ 6 ] performed a review on mHealth monitoring of pediatric asthma before and during the COVID-19 pandemic. Their scoping review identified 25 articles reporting the use of synchronous and asynchronous mHealth in pediatric asthma but only one article addressed asthma management, i.e., monitoring physical activity of asthmatic children during COVID-19 [ 15 ].…”
Section: Mhealth Covid-19 and Bibliometric Analysismentioning
confidence: 99%
“…Specifically, 1125 documents were officially published during the period 2020–2022 when a keyword search using [“mHealth” OR “mobile health”] and “COVID-19” was conducted on 7 January 2023, implying that about one-eighth of mHealth (or mobile health) publications were related to COVID-19 in both 2021 and 2022. Among the 1125 documents, 62 were systematic reviews, such as [ 5 , 6 , 7 , 8 , 9 ], i.e., literature reviews that uses systematic and explicit methods to identify, select, and critically appraise previously published studies with a clearly defined objective or research question [ 10 ]. Yet most of these 62 documents focused on a specific issue and selected only a small number of publications in their reviews [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation